Ventilator-induced barotrauma in critically ill patients with COVID-19: a retrospective observational study - Anuraag Sah; Emilio J. Fabian; Carlos Remolina (Greater Baltimore Medical Center, 2021)
Background: Ventilator-induced Barotrauma is a complication of intubation that is associated with high driving pressures and positive end-expiratory pressure use. We attempt to determine the incidence of barotrauma in intubated patients with SARS-CoV-2 infection. Methods: Retrospective observation case series of patients with SARS-CoV-2 infection who were intubated in the ICU. Data were collected for a total of 3 months from electronic health records on patient's age, sex, BMI, incidence of barotrauma, total length of intubation and outcome. Results: Ninteen out of the 100 included patients developed barotrauma as defined by radiographic evidence of pneumothorax, pneumomediastinum or subcutaneous emphysema. The average BMI of patients with barotrauma was 32.06 kg/m2 with an average age of 56.84 years and 9 patients being classified as obese (BMI ≥30 kg/m2). Fourteen out of 19 patients (73%) with barotrauma were intubated for 10 or more days with a median of 16.52 days. The overall mortality rate was noted to be 92% amongst intubated patients. Conclusion: Rate of barotrauma in COVID-19 intubated patients was noted to be 19% in our study, which is on par with the rate of ventilator-induced barotrauma with the previous SARS virus-associated ARDS, and higher than that of the general population with ARDS. Patients who developed barotrauma were also noted to be intubated for a significantly longer duration (16.52 days) as compared to their non-barotrauma counterparts. These findings suggest a need for more data and randomized studies to establish appropriate ventilator management strategies for patients with lung injury associated with COVID-19.